2013
DOI: 10.1037/a0030829
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effects on old-age cognitive functioning: A population-based study.

Abstract: Associations between genotypes and cognitive outcomes may provide clues as to which mechanisms cause individual differences in old-age cognitive performance. We investigated the effects of five polymorphisms on cognitive functioning in a population-based sample of 2,694 persons without dementia (60-102 years). A structural equation model (SEM) was fit to the cognitive data, yielding five specific latent factors (perceptual speed, episodic memory, semantic memory, category fluency, and letter fluency), as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
124
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 126 publications
(139 citation statements)
references
References 76 publications
11
124
2
2
Order By: Relevance
“…As previously reported (25,26), differences were observed across regions and cognitive tasks, demonstrating both a birth cohort gradient, with later cohorts (younger age) performing at higher levels than earlier cohorts (older age), and a geographic skill gradient, indicating a northern advantage over central and southern regions (Fig. 1 A-I).…”
Section: Resultssupporting
confidence: 50%
“…As previously reported (25,26), differences were observed across regions and cognitive tasks, demonstrating both a birth cohort gradient, with later cohorts (younger age) performing at higher levels than earlier cohorts (older age), and a geographic skill gradient, indicating a northern advantage over central and southern regions (Fig. 1 A-I).…”
Section: Resultssupporting
confidence: 50%
“…Subsequently this association has been replicated in two other independent studies in both adolescents and older adults (Jacobsen, Picciotto, Heath, Mencl, & Gelernter, 2009;Laukka et al, 2013). The mechanism/s by which these two polymorphisms (KIBRA rs17070145, CLSTN2 rs6439886) may influence episodic memory functioning is unclear.…”
Section: Introductionmentioning
confidence: 55%
“…Similarly, in older adults aged 79 years, the ε4 allele was associated with more rapid decline in verbal memory and abstract reasoning across 8 years (Schiepers et al 2012). Importantly, one study showed that the relationship of APOE to episodic memory and global cognition was attenuated, after exclusion of future dementia cases (Laukka et al 2013). This suggests that dementia-related processes may contribute to the link between APOE and cognition in old age.…”
Section: Apoe Polymorphismmentioning
confidence: 95%